Acclimation to short-term low temperatures in two Eucalyptus globulus clones with contrasting drought resistance - Costa E Silva, F.; Shvaleva, A.; Broetto, Fernando [UNESP]; Ortuno, M. F.; Rodrigues, M. L.; Almeida, M. H.; Chaves, M. M.; Pereira, J. S. (Oxford University Press, 2009)
We tested the hypothesis that Eucalyptus globulus Labill. genotypes that are more resistant to dry environments might also exhibit higher cold tolerances than drought-sensitive plants. The effect of low temperatures was evaluated in acclimated and unacclimated ramets of a drought-resistant clone (CN5) and a drought-sensitive clone (ST51) of E. globulus. We studied the plants' response via leaf gas exchanges, leaf water and osmotic potentials, concentrations of soluble Sugars, several antioxidant enzymes and leaf electrolyte leakage. Progressively lowering air temperatures (from 24/16 to 10/-2 degrees C, day/night) led to acclimation of both clones. Acclimated ramets exhibited higher photosynthetic rates, stomatal conductances and lower membrane relative injuries when compared to unacclimated ramets. Moreover, low temperatures led to significant increases of soluble Sugars and antioxidant enzymes activity (glutathione reductase, ascorbate peroxidase and superoxide dismutases) of both clones in comparison to plants grown at control temperature (24/16 degrees C). Oil the other hand, none of the clones, either acclimated or not, exhibited signs of photoinhibition Under low temperatures and moderate light. The main differences in the responses to low temperatures between the two clones resulted mainly from differences in carbon metabolism, including a higher accumulation of soluble Sugars in the drought-resistant clone CN5 as well as a higher capacity for osmotic regulation, as compared to the drought-sensitive clone ST51. Although membrane injury data suggested that both clones had the same inherent freezing tolerance before and after cold acclimation, the results also support the hypothesis that the drought-resistant clone had a greater cold tolerance at intermediate levels of acclimation than the drought-sensitive clone. A higher capacity to acclimate in a short period can allow a clone to maintain an undamaged leaf surface area along Sudden frost events, increasing growth capacity. Moreover, it can enhance survival chances in frost-prone sites expanding the plantation range with more adaptive clones.
Keywords: antioxidant capacity; chilling; dehydration tolerance; freezing; solute accumulation